Pig macrophages with site-specific edited CD163 decrease the susceptibility to infection with porcine reproductive and respiratory syndrome virus - Kui XU; Yan-rong ZHOU; Hai-tao SHANG; Chang-jiang XU; Ran TAO; Wan-jun HAO; Sha-sha LIU; Yu-lian MU; Shao-bo XIAO; Kui LI (Journal of Integrative Agriculture, 2023)
Porcine reproductive and respiratory syndrome (PRRS) is recognized as one of the most infectious viral diseases of swine. Although Cluster of differentiation 163 (CD163) is identified as an essential receptor for mediating PRRS virus (PRRSV) infection, the important residues involved in infection on CD163 are still unclear. Therefore, it is very important to identify these key residues to study the mechanism of PRRSV infection and to generate anti-PRRSV pigs. In this study, we first generated immortalized porcine alveolar macrophage (IPAM) cell lines harboring 40-residues (residues 523–562, including R561 (arginine (R) at position 561)) deletion of CD163. PRRSV infection experiments showed that these IPAM cell lines were completely resistant to PRRSV infection. We then generated cloned pigs carrying CD163-R561A (an arginine (R) to alanine (A) substitution at position 561 of CD163). PRRSV challenge experiments in porcine alveolar macrophages (PAMs) isolated from the CD163-R561A pigs showed significantly lower susceptibility to PRRSV than that of CD163-R561 PAMs. Through this study, we show that CD163 523–562 contains essential residues for mediating PRRSV infection, and that CD163 R561 significantly contributes to PRRSV infection but is not essential for infection. These functional sites can therefore serve as new targets for understanding the mechanism of PRRSV infection. Furthermore, CD163-R561A pigs can be used as an important model for improving pig germplasm with resistance against PRRSV.